Recovery of intercalated Li and synthesis of reduced graphene oxide from graphite of spent Li-ion battery for supercapacitor application - Uppin, Bhagyashree; Sankannavar, Rohini; Kangutkar, Raju S.; Manjanna, Jayappa; Kolekar, Sanjay; Nayaka, Girish P. (Inorganic Chemistry Communications, 2025)
Spent Li-ion batteries (LIBs) are accumulating rapidly across the world. Anode portion of spent LIBs is comprised of graphite with a significant amount of intercalated Li. Thus, it serves as an important secondary resource of Li. Therefore, this study is focused on the eco-friendly recovery of Li from anode graphite and the conversion of recovered graphite (RG) into reduced graphene oxide (rGO) for its application in supercapacitors. The spent graphite (SG) was dissolved in 0.5 M oxalic acid with a solid-liquid ratio of 50 g L- 1 at 70 degrees C for about 90 min. Under given condition, 100 % Li was extracted from graphite. The dissolved Li was successfully recovered as Li2CO3. Further, RG was used as a precursor for the synthesis of GO and then converted to rGO by reduction with gallic acid under microwave irradiation. As synthesized rGO was used as an electrode material for supercapacitor application. The rGO electrode exhibited highest specific capacitance of 1211 F g- 1 at a current density of 4 mA cm- 2. It showed energy density 168.2 W h kg- 1 and power density 1000 W kg- 1 with stability up to 2000 cycles (90 % retention). Further, asymmetric solid-state device (rGO//activated carbon) was fabricated with polyvinyl alcohol - H2SO4 as electrolyte. It exhibited high energy density of 94 W h kg- 1 at a power density of 1200 W kg- 1 and cycling stability up to 1500 cycles with 86.20 % capacity retention. Hence, rGO synthesized from spent LIB provides an excellent electrode material for construction of supercapacitor devices.
Keywords: Graphite anode; Lithium recovery; Recovered graphite; rGO synthesis; Spent Li-ion battery; supercapacitor